Alih Media dan Pemindahan Arsip Inaktif Instansi X Republik Indonesia dalam Menunjang Pemindahan Ibu Kota Negara - Iqnatius, Yeremia; Lawanda, Ike Iswary (Khazanah: Jurnal Pengembangan Kearsipan, 2025)
The digitization of inactive records is carried out by Institution X in order to arrange inactive records for the move to the new national capital using the SRIKANDI application. The digitization of inactive records makes the transfer of records more eﬀective and eﬃcient. This study aims to describe the process the digitization of inactive records so that it is ready for arrangement and transfer, by examining obstacles and solutions to problems that occur during the process. This research uses a qualitative approach with a case study method and the data collection process is carried out through interviews, observations, and documentation of the research process. Conclusion on the process of displacement and the digitization of inactive records Institution X is a government records transfer program towards integration and collaboration. This program refers to the Regulation of the Head of ANRI regarding the transfer, transfer of media and inactive records that collaborate to materialize in the policy of accelerating the arrangement of records of ministries/institutions that will move to the Capital City of the Nusantara (IKN). The compliance of implementers and agencies with ANRI's records management procedures and strategies determines the success of the digitization of inactive records.